Dapagliflozin: first SGLT2 inhibitor for type 2 diabetes. Issue 12 (1st July 2013) - Chaplin, Steve; Wilding, John
Abstract Dapagliflozin (Forxiga) is the first SGLT2 inhibitor licensed for the treatment of type 2 diabetes. In our New products review, Steve Chaplin presents the clinical data relating to its efficacy and adverse events, and Professor John Wilding discusses its potential role in treatment.